2014
DOI: 10.1111/aepr.12044
|View full text |Cite
|
Sign up to set email alerts
|

Micro Price Dynamics during Japan's Lost Decades

Abstract: We study micro price dynamics and their macroeconomic implications using daily scanner data from 1988 to 2013. We provide five facts. First, posted prices in Japan are ten times as flexible as those in the US scanner data. Second, regular prices are almost as flexible as those in the USA and Euro area. Third, the heterogeneity of frequency and size of price change across products is sizable and maintained throughout the sample period. Fourth, during Japan's lost decades, temporary sales have played an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…In Japan, by contrast, even lower priced stores conduct very frequent temporary sales. As Sudo, Ueda, and Watanabe () point out, prices in Japan are revised 10 times more frequently than those in the United States due to frequent temporary sales . Although these differences yield different results from Coibion, Gorodnichenko, and Hong's () study of the link between unemployment and the frequency of sales, the effect of unemployment on the average prices consumers pay (effective prices) is in the same direction in both cases.…”
Section: Evidence For Endogenous Bargain Huntingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, by contrast, even lower priced stores conduct very frequent temporary sales. As Sudo, Ueda, and Watanabe () point out, prices in Japan are revised 10 times more frequently than those in the United States due to frequent temporary sales . Although these differences yield different results from Coibion, Gorodnichenko, and Hong's () study of the link between unemployment and the frequency of sales, the effect of unemployment on the average prices consumers pay (effective prices) is in the same direction in both cases.…”
Section: Evidence For Endogenous Bargain Huntingmentioning
confidence: 99%
“…See, for example, Bils and Klenow () and Nakamura and Steinsson () for the United States and Sudo, Ueda, and Watanabe () for Japan.…”
mentioning
confidence: 99%
“…Finally, confirm whether output at the modified AS−AD equilibrium could expand. Equation (14) shows that where > 1 holds, productivity growth lowers the equilibrium level of the output, but we could avoid this if the money supply grew. This policy, which ensures a larger , means both equilibrium output and equilibrium inflation will be positive.…”
Section: The Modified As−ad Equilibriummentioning
confidence: 99%
“…In a somewhat different analysis, Sudo et al [14] used daily scanner price data to decompose the price changes to find that retail shops (or suppliers) play an important role in Japanese price dynamics. This focus on suppliers supports our emphasis on the supply side of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent empirical studies on microprice-setting as surveyed by Klenow and Malin [9] have uncovered the hitherto little known dynamics of microprices (Ref. [10], for Japan). Bils and Klenow [11], for example, by examining the frequency of price changes for 350 categories of goods and services, demonstrated that half of the prices remain valid for 5.5 months or less.…”
Section: Introductionmentioning
confidence: 99%